(untitled) (Research, Society and Development, 2020)
Chlamydia trachomatis (CT) is the most common of sexually transmitted infections (STIs) by bacteria worldwide. In Brazil, health services that systematically offer research for this bacterium as part of a gynecological or prenatal consultation are rare. The objective of this study was to verify the relationship of Chlamydia trachomatis as a risk factor for premature birth, through the changes presented during the pregnancy period, the need for preventive measures during prenatal care. This study is part of a systematic literature review with a qualitative approach with thematic focused on the possible correlation between Chlamydia trachomatis infection in pregnant women and premature birth and the importance of prenatal care in preventing this infection. When surveying the profile of the study, it was found that the prevalence is within the range reported worldwide. Prenatal follow-up is of great importance for the detection and treatment of this STI for both the newborn and the mother, one of the factors that still imply for this early and extremely important diagnosis is the examination as a form of screening that does not is made available by SUS. Through the main findings in the studies, CT infection shows a positive association with prematurity.